Trends in the growth of Japanese international banking in Western Europe - F. N. Burton; F. H. Saelens (Intereconomics, 1983)
Changes in Japan's domestic economy and the emergence of stronger trade and investment links between Japan and the world economy have created substantial pressures for her banks and other financial institutions to expand overseas. The following article examines trends in Japanese international banking since the beginning of the 1970s and, in particular, the growing presence of Japanese banks in Western Europe.
Keywords: 330; Japan